(untitled) (Economic and Political Thought, 2014)
The article lets its readers get acquainted with some theoretical issues. It aims to systemise the knowledge of an organisation’s sensitivity from an interdisciplinary perspective and present the authors’ proposal for instruments measuring an organisation’s sensitivity towards its employees. Making use of the output of psychology, the authors introduce the categorization into sensory, emotional and social sensitivity of organisations. Within each of them, they indicate specific activities that, on the one hand can be a proof for the existence of one type of sensitivity, and on the other hand a hint for the management staff as to how to build and/or strengthen an organisation’s sensitivity. They show that an organisation’s sensitivity is necessary and it lays a foundation for the implementation of the idea of the common good.